Pemberdayaan Masyarakat untuk Membangun Kemandirian Desa dengan UMKM Pemberdayaan Kesejahteraan Keluarga (PKK) melalui Produk Bubuk Jahe - Afifah Afra Aulia; Adjie Anggito Abhimanyu; Adam Ghani, Azizah; Azizah, Azizah; Hanung Kurniawan; Joko Tri Nugraha (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
This community service activity was motivated by the potential of the PKK MSMEs of Tawangsari Village, Tembarak, with local products Wedhang Jahe, which faced obstacles in business legality, product innovation, digital marketing, and non-cash payments. The main objective is to increase the competitiveness of MSMEs through digitalization and strengthening business legality, with a focus on training on NIB (Business Identification Number), QRIS, packaging innovation, and digital marketing strategies. Although the socialization and training were successful in increasing partners' understanding of digitalization and legality, the full implementation of the main agenda (NIB, QRIS, e-commerce) has not been realized due to the limited authority of the production division that is the partner. However, the high enthusiasm of partners shows positive prospects, concluding that strengthening MSMEs through product innovation and digital adaptation is a strategic step for village economic independence.